Post‐TAVR Ventricular Septal Defect in the Presence of Subaortic Membrane. Issue 3 (17th October 2014) - Lee, Christina W.; Hegde, Sheila M.; Ewer, Steven M.; Lozonschi, Lucian
Mini‐Abstract Transcatheter aortic valve replacement (TAVR) has traditionally been reserved for patients who are high‐risk with significant comorbid conditions. We present a case of an 80‐year‐old female who sustained a small, restrictive ventricular septal defect (VSD) following TAVR. This patient was thoroughly evaluated preoperatively and the decision was made to proceed with nonconventional repair given significant comorbid conditions in conjunction with subvalvular stenosis secondary to a subvalvular membrane. The objective of this presentation is to direct special focus to the echocardiographic images of this unique case in the setting of this unique anatomic variant.